Achalasia Following SARS-CoV-2 Infection: A Case Report and Review of Literature - Huang, Jianbin; Su, Huang; Lin, Jiejun; Zhu, Fangchao; Jiang, Xiaofen; Pan, Jie (Zeitschrift für Gastroenterologie, 2024)
Rationale The COVID-19 pandemic caused by the SARS-CoV-2 virus has led to health complications beyond respiratory symptoms, revealing multi-organ involvement, including potential gastrointestinal implications.Patient Concerns We present a case of a 40-year-old female without any history of achalasia who developed symptoms of the condition following a confirmed SARS-CoV-2 infection. Unusually, multiple esophageal ulcers were identified, which are not typically associated with achalasia.Diagnosis Achalasia and esophageal ulcers were confirmed through a series of examinations, including barium swallow, CT scan, and upper endoscopy. Furthermore, immunohistochemical staining of esophageal biopsy specimens revealed the presence of the SARS-CoV-2 spike protein, suggesting direct viral involvement.Interventions The patient was treated with calcium channel blockers and proton pump inhibitors and later underwent a peroral endoscopic myotomy (POEM) procedure following the resolution of her COVID-19 infection.Outcome After the POEM procedure, the patient made a good recovery.Lessons This case underscores the potential for SARS-CoV-2 to trigger gastrointestinal complications and emphasizes the need for ongoing patient management and further research into the long-term implications of COVID-19. Despite the single-case nature of this report, it contributes to the expanding understanding of the diverse and multi-systemic impact of COVID-19.
Keywords: SARS-CoV-2; COVID-19; achalasia; gastrointestinal complications; esophageal ulcers